BATIK DESIGN TRAINING SEBAGAI UPAYA PEMBEKALAN SOFT SKILL DI BIDANG DESAIN GRAFIS TERHADAP SISWA-SISWI SMK NEGERI 5 KOTA BENGKULU - Ernawati Ernawati; Funny Farady Coastera; Yuli Rodiah (DHARMA RAFLESIA, 2018)
Students of SMK Negeri 5 Bengkulu are given batik skills provision in Textile Craft Competence since 1995. The quality of students’ batik production, especially batik Basurek, has been recognized nationally. Traditional batik skills can be coupled with insight into computer graphics. As the generations facing the global market, batik craftsmen are charged to be more creative using technology in developing their business. Implementation method of the community service program is the method of knowledge transfer to the students and applying the concept of graphic design by using Adobe Photoshop. Direct practice using the computer and debriefing between instructor and participants help participants in understanding of training material. Evaluation are conducted by comparing the results of observations before and after training. From the results of the evaluation we concluded that trainees are already able to understand the basic functions of the software Adobe Photoshop and using it to design batik. Keywords: adobe photoshop, batik basurek, graphic design, senior high school student